A case report of a primary apocrine adenocarcinoma of the eyelid with literature review. (3rd September 2018) - Pagano Boza, C.; Vigo, R.; Premoli, J. E.; Croxatto, J.; Gonzalez Barlatay, J.
ABSTRACT: Introduction : Primary Apocrine adenocarcinomas (PAA) are very infrequent tumors that are often confused initially with benign lesions. Little is known about this disease and there is still much to be clarified. We present a case of PAA on the eyelid successfully treated with surgery alone and a literature review regarding what is currently described about this disease. Methods : Noncomparative, retrospective case report of a patient with PAA on the eyelid succesfully treated with surgery alone and a literautre review. Results : A 91-year-old man with a 2 months lesion on the upper left eyelid was treated with surgery alone with oncological margins of 5mm. The Hystopathology diagnosis was a PAA of the eyelid and free margins were obtained. After 12 months of follow-up, the patient does not show any signs of local recurrence or distant metastasis. A review of the literature suggests these tumors are located more frequently in the axilla (50%) and secondly in the head and neck (35%), with similar distribution in the upper (41%) and lower eyelid (45%). The most commonly used treatment is surgical excision, but radiotherapy and chemotherapy have also been used with variable results. Conclusions : PAA is a very rare and aggressive tumor. Because it is so infrequent, treatments are based on the sporadic cases encountered in the literature. As more cases are reported, more can be elucidated about the characteristics of this tumor, its behavior and best treatment choice and this may allow progress in the understanding and management of this disease.